PENYULUHAN ZAKAT DAN WAKAF DIGITAL BAGI SANTRI - Muzayanah; Khoirun Nisa; Izzatun Nafis; Agisca Arifien (DEVELOPMENT: Journal of Community Engagement, 2023)
The digital literacy gap among santri (Islamic boarding school students) regarding digital zakat and waqf poses a challenge to optimizing Islamic philanthropy in the modern era. This community service program aims to enhance santri's knowledge, skills, and awareness of the concepts, mechanisms, and security of digital zakat and waqf transactions. This activity employed a quasi-experimental method with a one-group pre-test/post-test design involving 45 santri at Arrahman Cidadap Islamic Boarding School. Data were collected through a knowledge test questionnaire before and after the counseling session, then analyzed using descriptive statistics and a paired-sample t-test. The results indicated a statistically significant increase in understanding. The participants' mean score rose from 45.70 on the pre-test to 82.50 on the post-test, with a significance value of (p <.001). This finding proves that an interactive and applicative counseling program is effective in bridging traditional fiqh understanding with modern digital competencies, positioning it as a strategic empowerment model for the pesantren community.